Soft law, responsibility and the biopolitics of front-of-pack food labels. Issue 3 (3rd July 2017) - Murphy, Brendon; Sanderson, Jay
ABSTRACT: Front-of-pack (FOP) food labels are increasingly used by government and industry to provide nutrition information to consumers for the promotion of healthier eating habits. However, quantitative and qualitative research into the effectiveness of FOP food labelling schemes is in its infancy and, at this stage at least, is largely unconvincing. Using Australia's health star rating system as an exemplar, in this article we provide a novel perspective on FOP food labels and in so doing make two (related) arguments about FOP food labels and in many ways about food label schemes more broadly. The first argument is that FOP food labels enliven a combination of hard and soft law. The second argument, informed by Foucault's notion of governmentality, is that FOP food labelling functions as a technology of the self. Drawing these two arguments together, we conclude that FOP food labels rely on a distorted rationality, because (i) the main actors in the process – food companies – are placed in a position of self-regulatory actors, fundamentally oriented to an economic rather than biopolitical agenda; and (ii) the biopolitics of population health through FOP food labels assumes particular kinds of rational consumers, when the reality of social life is far more complex.